Controlling laser sensor using LabVIEW - Tang, Nichelle Xin Hui (Nanyang Technological University, 2023)
The goal of this study is to use LabVIEW to create a data acquisition system that can collect data more quickly. The traditional data acquisition system takes a lot of time and employs a large number of people to run. This study suggests a brand-new, more effective, and minimally interventionist data acquisition system. LabVIEW, a potent graphical programming language frequently used for data acquisition and control systems, was used to create the proposed system. The system can gather data quickly, which cuts down on the time needed to gather data from experiments. Various data acquisition scenarios are used to test and assess the system. The findings demonstrate that the proposed system can collect data more quickly than the established system. Additionally, the system requires less human involvement, which lowers the possibility of mistakes during the data collection process. Overall, the proposed system is a promising replacement for current data acquisition methods because it is more effective, needs fewer personnel, and can gather data at a rapid rate.